Respostas

2013-06-01T11:35:43-03:00

x + x+r + x + 2r = 12

3x + 3r = 12

x + r =4( guarda isso)

 

 

x² + ( x+r)² + ( x+ 2r)² = 50

x² + x² + 2xr + r² + x² + 4xr + 4r² = 50

3x² + 4r² + 6xr = 50

 

 

sistema

 

*V= raiz quadrada
x + r = 4( eleva ao quadrado)

3x² + 4r² + 6xr = 50

 

 

 

x² + 2xr + r² = 16(x3)

3x² + 6xr + 4r² = 50

 

3x² + 6xr + 3r² = 48
3x² + 6xr + 4r² = 50(-)

 

0 +   0 - r² = -2

r= V2 

 

aí vc substitui na primeira equação:

x + x+r + x + 2r = 12

3x + 3r = 12

x + r = 4

x + V2 = 4

x = 4- V2

y = x +r = 4 - V2 + V2 = 4

z= x + 2r = 4 - V2 + 2V2 = 4 + V2

Espero ter ajudado =)

 

 

1 5 1